Relação entre níveis de atividade física, comportamento sedentário e o desempenho físico de pessoas idosas da comunidade: um estudo transversal - Silva, Milene Maria Branco (Universidade Federal de São Carlos, 2024)
Background: Regular physical activity (PA) is associated with the reduction of various adverse outcomes in aging. It is well-established that the practice of PA, especially of moderate to vigorous intensity (MVPA), is a successful strategy for healthy aging and the maintenance of physical performance in the older adults. Conversely, sedentary behavior (SB) is related to negative outcomes, and there is still a lack of studies clarifying whether light-intensity physical activity (LPA) has positive outcomes on physical performance. Objective: To assess the relationship between levels of PA with the physical performance of community-dwelling older adults. Methods: This is an observational and cross-sectional study. Older adults (≥ 60 years) participating in the "Geriatric Revitalization" extension project, with preserved ambulation capacity and a score > 18 points on the Mini-Mental State Examination, were included. PA levels (MVPA, LPA and SB) were assessed using the ActivPAL3™ micro accelerometer, and physical performance was evaluated through the 30-second sit-to-stand test, hand grip strength test, and Timed Up and Go test. Pearson or Spearman correlation tests were used to assess the correlation between PA and SB levels and physical performance variables. Subsequently, to evaluate the difference in physical performance between older adults who achieved 150 minutes of MVPA compared to those who did not, the Student's t-test or Mann-Whitney U test was conducted. Analyses were performed using JAMOVI Software (version 2.3.18), and statistical significance was set at p < 0.05. Results: A total of 45 older adults (73.78 ± 6.55 years and 73.3% female) were included in the study. No statistically significant correlations were observed between PA and SB levels and physical performance variables (p > 0.05). Despite the group of older adults who achieved 150 minutes of weekly MVPA showing better physical performance results compared to the group that did not reach the 150 minutes of weekly MVPA, no significant differences were found (p > 0.05). Conclusion: No significant correlations were found between PA levels and the physical performance of older adults. Additionally, there were no significant differences in the physical performance of older adults who achieved 150 minutes of weekly MVPA compared to those who did not.
Relationship between physical activity levels, sedentary behavior and performance physical function of older people in the community: a cross-sectional study
Keywords: Envelhecimento; Pessoas idosas; Atividade física; Comportamento sedentário; Desempenho físico; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL